Evaluasi Program Pemberdayaan Usaha Mikro Kecil dan Menengah (UMKM) LAZISMU Magetan dengan Pendekatan Diagram Kartesius - Azhar Alam; Harun; Nisrina Mar-atus Sholihah; Aditya Nurrahman (Department of Islamic Economics, IPB University, 2021)
This study aimed to determine the effect of zakat empowerment with MSMEs on the economic people empowerment according to the mustahik perceptions. This research used descriptive analysis with Cartesian coordinate approach. The results showed that the quality of LAZISMU in the MSMEs empowerment program in each dimension of tangible, reliability, responsiveness, assurance, and empathy was almost entirely good quality. The tangible dimension can be shown through the ease of procedures for submitting assistance and the period of its realization. The suitability between everything described by the officer with the reality on the reliable dimension is the main priority factor. The politeness, friendliness and communication skill of officers in the empathy dimension are factors that must be maintained. While transparency in providing information on survey results on the assurance dimension is a low priority factor. The monitoring on the impact of empowerment on the responsiveness dimension and the strategic location of the LAZISMU office on the tangible dimension was considered excessive. There is an effect of zakat empowerment with MSMEs on increasing the people's economic income in terms of service quality according to the perceptions of mustahik. This research suggests LAZISMU Magetan for accelerates the realization of assistance proposals and the ease in applying for assistance.